The Determining Factors Influences Student Gold Investing Interest - Muttaqin, Aminnullah; Aziza Berlian Putri (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
The purpose of this research is to determine the phenomena of student interest in gold investing following the COVID-19 pandemic. This study determines market targets, product development, and financial services. This quantitative research method collects data through a questionnaire. A total of 181 students were sampled using a random sampling technique. The study's findings indicate that financial literacy and investment motivation favor and significantly affect interest in gold investing. Meanwhile, income has a small but beneficial effect on interest in gold investment. If income affects students' interest in investing in gold at Brawijaya University, the income variable cannot be established realistically. According to observations, because the revenue obtained is sufficient for daily necessities, the amount of income is still supported by parents, and it is not easy to continuously save gold because funds are prioritized for other purposes or investments.